People's Movements in the 21st Century Risks, Challenges and Benefits - Muenstermann, Ingrid (IntechOpen, 2017)
The UNHCR assures us that never before have there been so many people on the move at the same time, mainly because of war-inflicted circumstances. Authors from different reputed institutions share their knowledge on this open-access platform to disseminate their knowledge at the global level. This book captures issues involved in meeting the challenges of people's movements in the twenty-first century. It explores attitudes of previously colonized people in a post-colonial period, analyses food insecurity in Canada, quality of life of elderly Turkish and Polish migrants in Germany, suicidal behaviours of immigrants admitted to an Italian-teaching hospital, and migration from a public healthcare perspective and points to the problem of tuberculosis among immigrants. Challenges of a more personal nature relate to second-language learning and acculturation of Brazilian migrants in Portugal and Asians as model minorities. Empirical evidence of why immigrants leave Norway is provided, and there is a discussion on the new actors of international migration (foreign students). This book closes with the voices of trailing women when it comes to the decision to emigrate. The collective contributions from experts attempt to provide updates regarding ongoing research and developments pertaining to migration.